Tingkat Kesadaran Hukum tentang Kepemilikan Administrasi Kependudukan pada Penduduk Miskin Desa Rowotamtu Kecamatan Rambipuji Kabupaten Jember - Solehati Nofitasari (JURNAL RECHTENS, 2018)
Civil registration is the right of every citizen in the sense of obtaining an authentic deed from a state official. Complete self-data at this time is a need that cannot be rejected or avoided by every citizen, including in Indonesia. The Indonesian state is currently improving itself to be able to perfect the data of each of its residents perfectly and accordingly. This need is very urgent with the presence of the era of digitalization that has penetrated every line of community life. Improvement and improvement of the population's self-data in theory and procedures is indeed very easy and does not require a long time. Every population and civil registration service has tried to provide solutions and innovations that are very varied, for the sake of holding one electronic ID card. The number of beneficiaries of the Family Hope Program in Rowotamtu village is 222 households and out of 222 beneficiaries who have only 70% of the electronic KTP, there are still many who have wrong names, are damaged and 30% are still in the old KTP format. ID cards are only one of the types of population administration and they are still many who do not understand their usefulness, especially if we see ownership of the Family Card there are still many names that have died are still not crossed from the Family Card. This means that awareness of ownership of population administration is still very minimal in Rowotamtu village. Based on the results of interviews through questions and answers in the socialization and quisoner of underprivileged communities in Rowotamtu Village, they assumed that they did not know the type of population administration and even the function of each type of population administration itself.